983 Patient's Satisfaction of Virtual Clinics for Post-Cardiothoracic Surgery Follow Up During COVID. (4th May 2021) - Durand-Hill, M; Ikenna Ike, D; n Bhardwaj Shah, A; Nijhawan, Aditi; Smith, Alex; Shipolini, Alex; Stamenkovic, Sasha
Abstract: Introduction: With advances in technology, virtual clinics are becoming increasingly attractive as a tool for outpatient follow up care. During the COVID-19 pandemic, the implementation of virtual outpatient clinics was crucial, for continued service provision despite social distancing guidelines. We aimed to ascertain patient satisfaction with virtual clinics in cardiothoracic surgery. Method: Forty patients who attended virtual clinics, post cardiothoracic surgery, were invited to provide feedback by means of a questionnaire. Feedback was gathered by junior doctors. Results: Thirty-four patients (20 had never had a telephone clinic appointment) agreed to provide feedback. Fifty percent of patients had not been seen since their operation. 91.2% (n = 31) of patients felt that the telephone consultation met their expectations/needs. Patient reported advantages of telephone consultations included: less concern regarding exposure to infection, no concern regarding parking, no travel time and less time off work. 79.4% (n = 27) would have preferred a face-to-face appointment. Patient reported disadvantages of telephone consultations were poor reception, felt they weren't listened to and would have preferred to have been physically examined. Conclusions: Patients were satisfied with telephone clinics for routine follow up post cardiothoracic surgery. However, the majority would have preferred face to face appointments.